If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 7 = 7(x + -2) Reorder the terms: 7 + y = 7(x + -2) Reorder the terms: 7 + y = 7(-2 + x) 7 + y = (-2 * 7 + x * 7) 7 + y = (-14 + 7x) Solving 7 + y = -14 + 7x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + y = -14 + -7 + 7x Combine like terms: 7 + -7 = 0 0 + y = -14 + -7 + 7x y = -14 + -7 + 7x Combine like terms: -14 + -7 = -21 y = -21 + 7x Simplifying y = -21 + 7x
| -10(b+645)=-490 | | 15-1/2b= | | 4w-60=440 | | 2g-17=1 | | y-6=6(x+6) | | 7xc=-3 | | 8x-1+15x+3x+9=360 | | Z+5=5 | | 5x+7(-x-14)=-88 | | 13x-30=9 | | 10x+3+3x+24=180 | | 24x^2+-12x+-12=0 | | 22/25-7/10 | | 5/20=30/x | | 8x-1+15x+3x+9=90 | | y+4=4(x+7) | | -7y-7=-5(y+5) | | Log(4x+12)=2 | | 72x+56=-84-37x | | 3u-5=10 | | 5/20=3-/x | | 8x-1+15x+3x+9=180 | | 8x-6y=56 | | Q/6--112=125 | | 0=-16x^2+560 | | -9/p-3=3/5 | | 12=-7v+5(v+6) | | y+7=4(x-9) | | 20+-6n=-12+-2n | | 2w+30=460 | | cos(0.5)x=-1 | | 1/3x^2-10=18 |